Drivers of Sectorial Export Earnings’ Performance in Nigeria: A Supply Leading Approach - Anastasia C. Onuorah, Francis Chigozie Okonkwo, Okafor Ikechukwu (International Journal of Advanced Science and Technology, 2020)
The paper investigated the supply leading drivers of sectorial export earrings’ performance in Nigeria from 1984 to 2018 using the ARDL Bound test and ECM approach. The regressed variable is drivers measured by import penetration, economic (trade) openness, foreign direct investment, exchange rate, and inflation rate while the regressor being sectorial export earnings’ performance were disaggregated into oil and non-oil earnings’ performance based on data derived from the Central Bank of Nigeria (CBN) Statistical Bulletin and World Bank Development index (2018). The result reported that only import penetration positively affected oil export earnings in the long run but in the short run, it adversely affected oil export earnings though FDI inflows passed the test of statistical significance. On the other hand, economic openness and stable inflation rate have a favourable effect on non-oil export earnings’ performance both on the long and short run. Again, while exchange rate and FDI inflows have a favourable effect on nonoil export earnings’ performance in the short run, in the long-run exchange rate has a negative insignificant effect on oil export earnings’ performance. However, only import penetration passed the test of significance both in the long and short run. To this end, we recommended, reduce tariffs and quota on imported industrial inputs to encourage continuous injection of foreign capital into the Nigerian non-oil sector. Again, continuous effort must be made to ensure that the present inflation and exchange rate is consistent with her export promotion strategy to ensure that the Nigerian naira is been not overrated.